2008
DOI: 10.1038/ismej.2008.9
|View full text |Cite
|
Sign up to set email alerts
|

Toward a mechanistic understanding of how natural bacterial communities respond to changes in temperature in aquatic ecosystems

Abstract: We examine how heterotrophic bacterioplankton communities respond to temperature by mathematically defining two thermally adapted species and showing how changes in environmental temperature affect competitive outcome in a two-resource environment. We did this by adding temperature dependence to both the respiration and uptake terms of a two species, two-resource model rooted in Droop kinetics. We used published literature values and results of our own work with experimental microcosms to parameterize the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 33 publications
4
95
2
Order By: Relevance
“…Long term (years) heating experiments in soils have shown that microbial activity returns to pre-warming values within a few years, likely due to a depletion of labile organic matter pools and/or thermal adaptation of the microbial community to the increased temperatures (e.g., Bradford et al, 2008;Rousk et al, 2012). Microbial temperature adaptation has also been demonstrated in lakes (Hall and Cotner, 2007;Hall et al, 2008) and similar mechanisms could also be at play in the ocean, but experimental data to support this are still missing.…”
Section: Implication For An Ocean Under Global Warmingmentioning
confidence: 99%
“…Long term (years) heating experiments in soils have shown that microbial activity returns to pre-warming values within a few years, likely due to a depletion of labile organic matter pools and/or thermal adaptation of the microbial community to the increased temperatures (e.g., Bradford et al, 2008;Rousk et al, 2012). Microbial temperature adaptation has also been demonstrated in lakes (Hall and Cotner, 2007;Hall et al, 2008) and similar mechanisms could also be at play in the ocean, but experimental data to support this are still missing.…”
Section: Implication For An Ocean Under Global Warmingmentioning
confidence: 99%
“…In a model, it has been shown that the effect of increasing temperature on bacterial community composition and bacterially mediated biogeochemical processes is linked to the resource stoichiometry of a given aquatic system (Hall et al 2008). It is possible that changes in size in relation to temperature also depend on the resource stoichiometry of the aquatic system.…”
Section: Effect Of Temperature On Cell Size and Morphology In Situmentioning
confidence: 99%
“…It was reported that warm-adapted bacteria could have lower minimal P cell quotas than do coldadapted bacteria (Hall et al 2008), which would confer an advantage to cells with low nucleic acid content (because nucleic acids are an important intracellular source of P) in warm-temperature and resource-limited environments (Van Wambeke et al 2011). The change of temperature, coupled with regional-scale latitudinal gradients or sometimes local weather contingencies, will affect microbial activity, metabolism and growth rate, and hence the abundance of LNA and HNA.…”
Section: Geographic Patterns In Abundance Of Lna and Hna Subgroupsmentioning
confidence: 99%